METABOLIC THERAPY IN PATIENTS WITH ISCHEMIC STROKE - L. B. Zavaliy; S. S. Petrikov; A. V. Schegolev (Неотложная медицинская помощь)
The article shows the world experience of metabolic therapy use in the treatment of ischemic stroke. The issue still remains prominent. The reasonability of prescribing metabolic drugs is not completely clear, its effectiveness has not been fully proved, despite numerous studies which show only trends. The article presents an overview of the most popular drugs of different pharmacological groups with a metabolic effect which affect different parts of the ischemic cascade. Ethylmethylhydroxypyridine succinate and cytoflavin have predominantly antihypoxic effect, improve functional outcome and neurological functions, and normalize overall well-being and adaptation. Cerebrolysin is a complex of low molecular weight biologically active peptides derived from the pig’s brain. It has a multimodal effect on the brain, helps to reduce the volume of cerebral infarction, restores neurologic functions and improves the functional outcome. Cortexin is a mixture of cattle brain polypeptides, also has a complex action that provides the most complete reversion of neurological deficit, improves cognitive functions and the functional outcome, reduces the level of paroxysmal convulsive readiness and improves bioelectric activity of the brain. Citicoline is a precursor of cell membrane key ultrastructures, contributes to significant reduction in the volume of cortical brain damage, improves cholinergic transmission, which results in better clinical outcome, even despite the questionable impact on the neurological status. Choline Alfoscerate is a precursor of choline, and the use of the drug significantly limits the growth of the cerebral infarction area starting from the first day of therapy, leads to reversion of neurological symptoms and achievement of rehabilitation goals. Actovegin is deproteinized derivative of calf blood, activates metabolism in tissues, improves trophism and stimulates regeneration. In a large study, it was shown that Actovegin improved cognitive function in patients who had experienced a stroke,. The drug does not significantly improve the neurological status of patients after a stroke, but it reduces the risk of the stroke development in the next 10 years. Thus, we analyzed mechanisms of medical substances action and data of experimental and clinical studies, including ones after thrombolytic therapy and with inclusion of drugs for primary and secondary prevention of ischemic stroke. The reasonability and effectiveness of prescribing a combination of drugs of different pharmacological groups affecting brain metabolism remains controversial, since the excessive drug treatment may have complications. The safety of metabolic therapy is in doubt, and some of authors views presented confirm the need for additional large independent studies.